Pengelolaan sedıaan metadon pada Program Terapı Rumatan Metadon (PTRM) dı satelıt pelayanan PTRM - Julaeha Julaeha; Nunung Priyatni; Rustamaji Rustamaji (Politeknik Kaltara, 2022)
Methadone is a type of synthetic narcotic that is used as substitution therapy in the Methadone Maintenance Therapy Program (MMTP). Therefore, methadone must be treated as narcotics in general. Pharmacists in MMTP have responsibility for the management of methadone. This study aims to evaluate the suitability of the management of methadone preparations at the MMTP satellite service in the Special Region of Yogyakarta (DIY) based on the MMTP guidelines issued by the Ministry of Health which include requests, storage, dispensing, and reporting of methadone use. This study is a mixed-methods study (qualitative and quantitative) with prospective data collection. The quantitative measurement instrument in the study was in the form of a checklist table for the suitability of methadone management based on applicable guidelines. Qualitative data sourced from interviews with MMTP officers. The results of this study indicate that the demand, storage, and reporting of the use of methadone are in accordance with the MMTP service guidelines. However, for the dispensing of methadone on the MMTP service satellites, it is still carried out by health workers other than pharmacists.